The Effect of Acute Urinary Retention on Serum Prostate-Specific Antigen Level - Aliasgari, Majeed; Soleimani, Mohammad; Hosseini Moghaddam, Seyyed Mohammadmehdi (Urology Journal, 2009)
Introduction: Our aim was to evaluate the effect of acute urinary retention on serum prostate-specific antigen (PSA) level. Materials and Methods: Men aged 50 years and older who presented with acute urinary retention were studied. Patients with urethral stricture, neurogenic bladder, prostate cancer, and those with a history of recent instrumentation or prostate biopsy were excluded. Blood samples for serum PSA measurement were obtained (PSA1), and an indwelling urethral catheter was inserted for 2 weeks. Before catheter removal, a second blood sample for measurement of serum PSA level (PSA2) was obtained. In patients who were able to void, a third sample was obtained 3 weeks later (PSA3). In the first and second visits, digital rectal examinations (DRE1, DRE2) were performed to assess prostate volume. Mean PSA levels (PSA1, PSA2, and PSA3) and prostate volumes (DRE1, DRE2) were compared. Results: Forty-five patients with a mean age of 70.18 years (range 56 to 85 years) participated in this study. Mean PSA1 and PSA2 levels were 9.8 ng/mL and 5.05 ng/mL, respectively (P < 0.001; medians, 6.2 and 4.2 ng/mL). Mean prostate volumes at the time of retention and 2 weeks later were 43.4 mL and 37.8 mL, respectively (P < 0.001; medians, 45 and 40 mL). PSA3 was measured in 31 patients 2 weeks after catheter removal. In this group of patients, mean PSA2 and PSA3 levels were 5.03 ng/mL and 4.97 ng/mL, respectively (P = 0.49; medians, 4.3 and 4.1 ng/mL). Conclusion: Acute urinary retention can increase serum PSA levels by approximately 2 fold. In this series, we found that this effect may continue up to 2 weeks.